Dinero, poder y política: financiamiento electoral como clave en la influencia de Odebrecht en Perú y México - Martinez Encarnación, Kenyi (2019)
Currently, Odebrecht is the most emblematic case of corruption in Latin America, involving dozens of politicians, businessmen and public works, including Peru and Mexico. However, the problem is not only about corruption, but it is behind a little known system, where the concern has to do with the "rules of the game" and their "players". Therefore, this article aims to explain why Odebrecht was able to influence Peruvian and Mexican states’ decisions about awarding public contracts. In that line, it is argued that they were for three reasons. First, their timely delivery was attractive to politicians, because they were effective in finishing the works before they finished their term; and, therefore, they can inaugurate them with an additional incentive ("good side of the company"). Second, another factor was its influence on the State, because they created a corruption net with the highest levels of government through electoral financing, bribes, lobbies and local constructions to win tenders ("dark side of the company"). In particular, electoral financing was key, because it creates the basis for later building a dangerous network in order to seek more power in politics through money. Third, a final factor was institutional weakness, because the Brazilian firm took advantage of a context of "tailor" laws that not only avoided audits and accountability, but also facilitated corruption as if they were made to the measures of the "client ". Finally, it explains these three factors from two megaprojects in Peru and Mexico: Metro de Lima Line 1 and Miguel Hidalgo Tula I Refinery.